2016
DOI: 10.1371/journal.pone.0157905
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Fragment of Agrin (CAF), a Novel Marker of Renal Function, Is Filtered by the Kidney and Reabsorbed by the Proximal Tubule

Abstract: Agrin, a multidomain proteoglycan and neurotrypsin, a neuronal serine protease, are important for forming (neuromuscular) synapses. Proteolytical activity of neurotrypsin produces a C-terminal fragment of agrin, termed CAF, of approximately 22 kDA molecular size which also circulates in blood. The presence of CAF in urine suggests either glomerular filtration or secretion into urine. Blood levels of CAF have been identified as a potential novel marker of kidney function. Here we describe that several nephron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Meanwhile, Goldberg et al reported that mice lacking agrin exhibited normal glomerular structure and normal renal function including glomerular function. Moreover, recent studies have demonstrated that CAF was likely cleared from circulation by glomerular filtration and subsequent endocytosis in the proximal tubule in their animal experiments. Thus, we could preliminarily infer that changes in serum CAF concentrations could most likely to be explained by extra‐renal source and decreased renal clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Goldberg et al reported that mice lacking agrin exhibited normal glomerular structure and normal renal function including glomerular function. Moreover, recent studies have demonstrated that CAF was likely cleared from circulation by glomerular filtration and subsequent endocytosis in the proximal tubule in their animal experiments. Thus, we could preliminarily infer that changes in serum CAF concentrations could most likely to be explained by extra‐renal source and decreased renal clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with stable COPD were included while those with unstable COPD (infection, exacerbation and/or hospitalization in the past month), arthritis, myopathies and neurological diseases were excluded [ 19 ]. Further, impaired renal function can reduce glomerular filtration and increase circulating levels of CAF [ 20 ]. However, our study cohort had no clinical or laboratory signs of renal failure.…”
Section: Methodsmentioning
confidence: 99%
“…214 In human beings, CAF was detected both in urine and blood, suggesting its role as a marker for renal clearance with increased serum levels indicating impaired kidney function. 215 In a study of 61 patients with severe sepsis and septic shock, serum levels of CAF were associated with AKI (AUC, 0.721) independent of sepsis. 216 Hepcidin is a 25-amino acid, cystein…”
Section: Q30mentioning
confidence: 99%